2014
DOI: 10.1177/0002716214541042
|View full text |Cite
|
Sign up to set email alerts
|

Performance Funding for Higher Education

Abstract: Since the 1970s, federal and state policy-makers have become increasingly concerned with improving higher education performance. In this quest, state performance funding for higher education has become widely used. As of June 2014, twenty-six states were operating performance funding programs and four more have programs awaiting implementation. This article reviews the forms, extent, origins, implementation, impacts (intended and unintended), and policy prospects of performance funding. Performance funding has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
159
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(164 citation statements)
references
References 18 publications
3
159
1
1
Order By: Relevance
“…A few mentioned that they felt the original goal of the policy was the tuition restraint provision and not actually focusing on changing institutional behavior in the realm of the metrics. This finding is different than previous research, which found that performance funding policies resulted in significant intermediate institutional change including academic and student service policies, programs and practices such as closing programs with low graduation rates, changing course content or sequences, increasing advising, changing retention programs and changes in financial aid (Dougherty et al, 2014a;Dougherty & Reddy, 2013). PAT highlights potential decision making processes that could play a role in this finding.…”
Section: Impactscontrasting
confidence: 79%
See 3 more Smart Citations
“…A few mentioned that they felt the original goal of the policy was the tuition restraint provision and not actually focusing on changing institutional behavior in the realm of the metrics. This finding is different than previous research, which found that performance funding policies resulted in significant intermediate institutional change including academic and student service policies, programs and practices such as closing programs with low graduation rates, changing course content or sequences, increasing advising, changing retention programs and changes in financial aid (Dougherty et al, 2014a;Dougherty & Reddy, 2013). PAT highlights potential decision making processes that could play a role in this finding.…”
Section: Impactscontrasting
confidence: 79%
“…the governmental relations office, the finance office, or the president). Previous research has found that performance funding policies struggle to be disseminated across institutions, with senior level administrators familiar with the policy but lower level administrators and faculty not aware of the specifics of the policy (Burke, 2005;Dougherty et al, 2014a;Freeman, 2000;Hall, 2000;Schaller, 2004). Therefore, this study focused on senior level administrators and excluded faculty and lower level administrators.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Extensive research has demonstrated how this has influenced policymakers throughout the U.S. at both the state and federal levels [50,73]. A popular state finance approach to incentivizing institutions to increase the number of college completers is performance-based funding [74]. Empirical research mostly finds a null or negative impact of pay-for-performance as it has thus far been implemented towards higher education [75].…”
Section: Discussionmentioning
confidence: 99%